Improving the Clinical Performance of Dental Implants Through Advanced Surface Treatments: The Case of Ti and ZrO2 Coatings - Mohamed Aissi; Qanita Tayyaba; Azzedine Er-Ramly; Hendra Hermawan; Nadia Merzouk (Metals)
This review summarizes the development of surface treatments applied to dental implants with the aim of improving their clinical performance. It covers the advancement of various techniques, from the conventional to the more advanced ones. Among the recent advancements, surface texturing has enabled atomic and structural modifications of implant surfaces at the micro- and nanoscales, improving tissue–material interactions. Acid etching and atomic layer deposition applied onto implant surfaces results in optimized osseointegration by stimulating the deposition and proliferation of osteoblasts and fibroblasts. The atomic layer deposition of TiO2, ZnO, ZrO2, and CaCO3 has proven effective in improving osseointegration and tackling corrosion. Corrosion is still an important issue, whereby metals released from titanium implants and their associated degradation products cause local and systemic side effects, leaving a wide avenue for future research. The development of hybrid dental implants is envisaged through new materials and technologies, such as additive manufacturing, which may play a critical role in the fabrication of patient-specific implants with tailored nano-topography capable of enhancing such properties as antibacterial activity and osseointegration.